In Refuge 22.1, the name of an author was misspelled on the contents page and on page 129. The correct spelling is Mahshid Esfandiari. - Refuge, Editor (Refuge: Canada’s Journal on Refugees, 2005)
Erratum: in Refuge 22.1, the name of an author was misspelled on the contents page and on page 129. The correct spelling is Mahshid Esfandiari.